High-dose-rate brachytherapy for prostate cancer in a previously radiated patient with polyethylene glycol hydrogel spacing to reduce rectal dose: case report and review of the literature - Nguyen, Paul; Devlin, Phillip M.; Beard, Clair J.; Orio, Peter F.; O'Leary, Michael P.; Wolfsberger, Luciant D.; O'Farrell, Desmond A.; Sweeney, Christopher M.; Hadaschik, Boris; Hohenfellner, Markus; Hatiboglu, Gencay (Brachytherapy, 2013)
Purpose - To describe the use of a temporary spacer to reduce rectal dose prior to prostate radiation in a man with prior pelvic radiotherapy and review the relevant literature. - Methods and Materials - A healthy 57-year-old man presented with high-risk prostate cancer (Gleason score of 8, prostate-specific antigen level [PSA] 12.6 ng/mL, T3a by magnetic resonance imaging [MRI]), only 2.5 years after a low anterior resection followed by pelvic chemo-radiotherapy to 50.4 Gy for a locally advanced rectal cancer. Due to the prior radiation, he was not felt to be a candidate for surgery or external beam radiation, so he chose long-term androgen deprivation therapy (ADT) plus high-dose-rate brachytherapy to 36 Gy in 6 fractions. To reduce the radiation dose to the anterior rectal wall, 10 mL of a polyethylene glycol hydrogel spacer was injected between the prostate and rectum and created between 1.4 and 1.5 cm of separation along the length of the prostate. - Results - Two randomized trials demonstrating that local therapy plus ADT improves overall survival compared to ADT alone provided the rationale for additional prostate radiotherapy in this otherwise healthy patient. Salvage brachytherapy is associated with a 3.4% rate of rectal fistula among the 251 cases reported in the literature from 2000-2007, with rates as high as 12% in one series. The spacer allowed the rectal dose constraint goals to be easily met. - Conclusions - Injecting an absorbable polyethylene glycol hydrogel to separate the prostate and rectum appears to be associated with decreased maximum and mean rectal doses, and may have particular utility in previously irradiated patients.